2018
DOI: 10.1177/1545968318776371
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Man Intrathecal Application of Neurite Growth-Promoting Anti-Nogo-A Antibodies in Acute Spinal Cord Injury

Abstract: ATI335 was well tolerated in humans; efficacy trials using intrathecal antibody administration may be considered in acute SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(86 citation statements)
references
References 46 publications
1
84
0
1
Order By: Relevance
“…Consistently, intrathecal administration of a Nogo-A neutralizing antibody following SCI resulted in enhanced axon growth and collateral sprouting in both rats and non-human primates (Merkler et al, 2001;Freund et al, 2006). These results led to a phase I trial (NCT00406016), which was completed in 2011 to assess the safety of intrathecal administration of ATI355 (Novartis), a recombinant human antibody directed against Nogo-A that was well-tolerated in patients with acute SCI (Kucher et al, 2018). Currently there are two ongoing phase II trials (NCT03935321 and EudraCT2016-001227-31) as a follow-up to this study, with no results posted.…”
Section: Modulating Glial Cell-axonal Growth Cone Interactions To Aidmentioning
confidence: 91%
“…Consistently, intrathecal administration of a Nogo-A neutralizing antibody following SCI resulted in enhanced axon growth and collateral sprouting in both rats and non-human primates (Merkler et al, 2001;Freund et al, 2006). These results led to a phase I trial (NCT00406016), which was completed in 2011 to assess the safety of intrathecal administration of ATI355 (Novartis), a recombinant human antibody directed against Nogo-A that was well-tolerated in patients with acute SCI (Kucher et al, 2018). Currently there are two ongoing phase II trials (NCT03935321 and EudraCT2016-001227-31) as a follow-up to this study, with no results posted.…”
Section: Modulating Glial Cell-axonal Growth Cone Interactions To Aidmentioning
confidence: 91%
“…With regard to therapeutic intervention, NogoA and other myelin-associated inhibitors have been extensively studied in their capacity as inhibitors of repair and have been identified as promising targets for therapeutic intervention, especially for the treatment of SCI 52-61 and stroke [62][63][64][65][66][67][68] . A NogoA neutralising antibody, IN-1, has been tested in rodent models of SCI 52,54,56,69 , followed by NHPs 58,70,71 , and finally human subjects 72 . The Phase I clinical trial using ATI335 (NogoA neutralizing antibody) in acute paraplegic and tetraplegic patients reported that it is well tolerated following intrathecal administration 72 and has entered Phase II trials in subacute SCI (ClinicalTrials.gov NCT03935321).…”
Section: Discussionmentioning
confidence: 99%
“…A NogoA neutralising antibody, IN-1, has been tested in rodent models of SCI 52,54,56,69 , followed by NHPs 58,70,71 , and finally human subjects 72 . The Phase I clinical trial using ATI335 (NogoA neutralizing antibody) in acute paraplegic and tetraplegic patients reported that it is well tolerated following intrathecal administration 72 and has entered Phase II trials in subacute SCI (ClinicalTrials.gov NCT03935321). In addition, a soluble NgR decoy blocking Nogo, MAG and OMgp ligands is efficacious preclinically in chronic SCI 73,74 , and has entered clinical trials for that indication (ClinicalTrials.gov NCT03989440).…”
Section: Discussionmentioning
confidence: 99%
“…A human phase-I safety and tolerability trial with intrathecal application of anti-Nogo-A antibodies in acutely spinal cordinjured patients has been concluded successfully (Kucher et al, 2018). A phase-two randomized controlled European multicenter trial testing for upper-limb motor recovery in acute tetraplegic patients is ongoing (https://nisci-2020.eu).…”
Section: Discussionmentioning
confidence: 99%